KERUKUNAN DALAM KEANEKARAGAMAN: Struktur Keberagamaan Masyarakat Pucakwangi - Mas'udi, Mas'udi (Jurnal THEOLOGIA, 2018)
This study aims to determine the religious structure of the community of Pucakwangi Village, Pucakwangi District, Pati Regency, Central Java Province. Religious awareness is an important foundation for the formation of religious harmony in diversity. With a qualitative functional structural approach, this study analyzes the structures that form community harmony in its diversity. The results of the study show some basic structures found in the midst of the diversity of the Pucakwangi Village community. Building an attitude of sympathy among followers of religion created with the participation of Christians in "tahlilan" activities, visiting each other in commemoration of religious holidays is another part of the forms of harmony they build together. Counteracting religious radicalism is another aspect of harmony that is built by the community with an awareness of the interÂrelationships of their recent lives with their ancestors.